2015
DOI: 10.1186/s13054-015-1049-8
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen administered after cardiac arrest and cardiopulmonary resuscitation ameliorates acute kidney injury in a sex- and age-specific manner

Abstract: Introduction: There is a sex difference in the risk of ischemic acute kidney injury (AKI), and estrogen mediates the protective effect of female sex. We previously demonstrated that preprocedural chronic restoration of physiologic estrogen to ovariectomized female mice ameliorated AKI after cardiac arrest and cardiopulmonary resuscitation (CA/CPR). In the present study, we hypothesized that male mice and aged female mice would benefit from estrogen administration after CA/CPR. We tested the effect of estrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 52 publications
(71 reference statements)
2
39
0
Order By: Relevance
“…Consistent with this finding, serum creatinine levels were significantly higher in aged versus young mice after CA/CPR (Figure 2D). Together, these data indicate that both brain and kidney sustained more severe damage in aged versus young mice in our CA/CPR model, which agrees with previous reports 15, 16…”
Section: Resultssupporting
confidence: 93%
“…Consistent with this finding, serum creatinine levels were significantly higher in aged versus young mice after CA/CPR (Figure 2D). Together, these data indicate that both brain and kidney sustained more severe damage in aged versus young mice in our CA/CPR model, which agrees with previous reports 15, 16…”
Section: Resultssupporting
confidence: 93%
“…However, Palmer BF conducted a review showing that since estrogens could regulate adipose deposition and function, males and postmenopausal females tended to deposit more visceral fat, while premenopausal females accrued subcutaneous fat, leading to the classic body shape which has been highly correlated to an increased chronic disease risk [36]. Animal studies have demonstrated that estrogen exerts renoprotective effects after whole-body acute alternatives of hemodynamics and estrogen doses improved the renal outcome in male rats [37]. In contrast, women had higher values of VAI, LAPI and WHtR compared with men in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…Rodriguez-Porcel et al demonstrated impaired kidney response to vasodilators (acetylcholine and sodium nitroprusside), but they used electron-beam computed tomography, which is difficult to implement routinely. 20 LDF has been extensively used to assess renal microcirculation in mice in ischemiareperfusion, 21,22 preconditioning, 23 renal cryoinjury 24 or other models. 25 LASCA and LDF both use laser speckle patterns, but the analysis techniques differ.…”
Section: Discussionmentioning
confidence: 99%